Intra-household Work Time Synchronization: Togetherness or Material Benefits? - Chris van Klaveren; Henriëtte Maassen van den Brink (Tinbergen Institute, 2005)
If partners derive utility from joint leisure time, it is expected that they will coordinate their work schedules in order to increase the amount of joint leisure. In order to control for differences in constraints and selection effects, this paper uses a new matching procedure, providing answers to the following questions: (1) Do partners coordinate their work schedules and does this result in work time synchronization?; (2) which partners synchronize more work hours?; and (3) is there a preference for togetherness? We find that coordination results in more synchronized work hours. The presence of children in the household is the main cause why some partners synchronize their work times less than other partners. Finally, partners coordinate their work schedules in order to have more joint leisure time, which is evidence for togetherness preferences.
Keywords: D13; I31; J12; J22; 330; Time Allocation; Leisure Time; Togetherness; Work Hours